Enteroviral central nervous system infections in patients with Lyme neuroborreliosis - Perlejewski, Karol; Radkowski, Marek; Pawełczyk, Agnieszka; Rydzanicz, Małgorzata; Dzieciątkowski, Tomasz; Makowiecki, Michał; Paciorek, Marcin; Welc-Falęciak, Renata; Horban, Andrzej; Laskus, Tomasz (Ticks and tick-borne diseases, 2023)
•Patients with Lyme neuroborreliosis are rarely examined for the presence of neurovirulent viruses.•Enteroviruses were identified in 13 % of patients with Lyme neuroborreliosis.•The possible co-occurrence of enterovirus and Lyme neuroborreliosis infections may warrant further research.•Metagenomic next-generation sequencing is prone to false signals. Patients with Lyme neuroborreliosis (LNB) are rarely tested for the presence of neurovirulent viruses other than tick-borne encephalitis virus (TBEV); however, such coinfections could be of clinical importance. The aim of the study was to search for the presence of neurotropic viruses in a LNB patients. Fourteen patients admitted with signs and symptoms of neuroinfection who were eventually diagnosed to have LNB (according to the guidelines of the European Federation of Neurological Societies) were subjects of the study. Sera and cerebrospinal fluid (CSF) collected at the time of initial presentation were tested for viral pathogens most common in our geographical area: human enteroviruses (EV), herpes simplex virus type 1 and 2, varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, human herpesvirus type 6, human adenoviruses, and TBEV using PCR/RT-PCR and serological assays. RNA and DNA-based metagenomic next-generation sequencing (mNGS) was used to detect other viral pathogens. EV was detected in CSF from two (14 %) LNB patients and viral loads were similar (220 and 270 copies/ml). The mMGS analysis were performed on CSFs from 10 patients and generated a total 213,750,885 NGS reads, 0.05 % of which were viral. However, none of potential pathogens fulfilled the criteria for positive viral detection by mNGS. Using a number of PCR/RT-PCR assays and mNGS we identified EV infection in two out of 14 LNB patients. The possible co-occurrence of enterovirus and Lyme neuroborreliosis infections may warrant further research.